Near-infrared emission properties and energy transfer of Tm3+-doped and Tm3+/Dy3+-codoped chalcohalide glasses - Gao Tang; Cunming Liu; Zhiyong Yang; Lan Luo; Wei Chen (Journal of Applied Physics, 2008)
Near-infrared emission properties of Tm3+ in GeSe2–Ga2Se3–CsI glasses were investigated. The increase in emission intensity ratio I1.47 μm/I1.22 μm and the large increase in the lifetime of the Tm3+:H34 level from 189 to 2480 μs can be obtained as CsI concentration changes from 20% to 40%. These improved emission properties result from the appearance of I-containing structural units, which have low phonon energy and are located near the Tm3+ ions, dominating the multiphonon relaxation and cross relaxation. Radiative parameters of Tm3+ were calculated based on the Judd–Ofelt analysis. The potential use of Tm3+-doped GeSe2–Ga2Se3–CsI glasses for S-band fiber amplifiers was discussed. Additionally, the intensity and lifetime of 1.2, 1.3, and 1.47 μm infrared fluorescence on Tm3+/Dy3+-codoped GeSe2–Ga2Se3–CsI glasses were studied, and the energy transfer mechanisms were discussed.